Regulating Data Monopolies A Law and Economics Perspective - Ma, Jingyuan (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book analyzes the business model of enterprises in the digital economy by taking an economic and comparative perspective. The aim of this book is to conduct an in-depth analysis of the anti-competitive behavior of companies who monopolize data, and put forward the necessity of regulating data monopoly by exploring the causes and characteristics of their anti-competitive behavior. It studies four aspects of the differences between data monopoly and traditional monopolistic behavior, namely defining the relevant market for data monopolies, the entry barrier, the problem of determining the dominant position of data monopoly, and the influence on consumer welfare. It points out the limitations of traditional regulatory tools and discusses how new regulatory methods could be developed within the competition legal framework to restrict data monopolies. It proposes how economic analytical tools used in traditional anti-monopoly law are facing challenges and how competition enforcement agencies could adjust regulatory methods to deal with new anti-competitive behavior by data monopolies.
Introduction -- The form of Data Monopoly -- Defining Relevant Market for Data Monopoly -- Entry Barriers of Data Monopoly -- Abuse of Dominant Position -- The Impact on Consumer Welfare -- Conclusions.
Keywords: Private international law; Conflict of laws; International law; Comparative law; Commercial law; Law and economics; Private International Law, International and Foreign Law, Comparative Law; Commercial Law; Law and Economics